Gene Silencing Therapies for Huntington’s Disease - Chunlan Hao; Hanfeng Ji (Neurology Letters)
Huntington’s disease (HD) is a rare, autosomal‑dominant neurodegenerative disorder precipitated by a pathological expansion of CAG trinucleotide repeats in exon 1 of the huntingtin (HTT) gene. Mutant huntingtin (mHTT) imposes a toxic gain‑of‑function that progressively compromises neuronal circuitry, culminating in the distinctive triad of motor, cognitive and psychiatric symptoms. In the absence of disease‑modifying agents, HTT‑lowering strategies have emerged as one of the most vigorously pursued therapeutic concepts in modern neuroscience. Gene silencing can be achieved at the transcriptional, post‑transcriptional or translational level using chemically modified antisense oligonucleotides (ASOs), RNA‑interference (RNAi) triggers, adeno‑associated virus (AAV)‑delivered microRNAs, small‑molecule splice modulators, and precision genome‑ or transcript‑editing tools such as CRISPR and zinc‑finger protein transcriptional repressors. This review provides a comprehensive, critical and up‑to‑date synthesis of pre‑clinical evidence, clinical progress and translational challenges associated with each modality. We discuss platform‑specific delivery hurdles, pharmacokinetic profiles, pharmacodynamic biomarkers, safety liabilities and emerging regulatory frameworks. Findings from the halted GENERATION‑HD1 tominersen programme are re‑examined to define optimal dosing windows and patient‑selection criteria. We conclude by highlighting next‑generation approaches, including base editing, allele‑selective cocktails and multimodal combination regimens, that may converge on durable disease modification.